BLOOD PRESSURE AND BODY MASS INDEX OF WORKERS OF THE REGIONAL ELECTORAL COURT – MS (Fiep Bulletin - online, 2013)
The nutritional disorders such as overweight and obesity, hypertension and sedentary lifestyle are major concerns of public health in Brazil, being important risk factors for chronic non-communicable diseases. Therefore the objective of the present work is to determine the correlation between body mass index (BMI) and blood pressure (BP) of individuals of both sexes, who work in Regional Electoral Court in Campo Grande - MS. The sample was composed of 125 individuals, 62 women and 63 men. To obtain data was measured body weight and height equalizing the values of BMI = weight/height2, while the blood pressure was measured using the aneroid blood pressure device WANMEDC (stethoscope of 1 head). With the obtained results we observed that the classification of women in relation to Eutrophic BMI was 64.52 % and obesity in worrying levels of 11.29 % (Obesity Classes I, II and III). In men these same rates were 30.16 % and 30.16 % respectively. Our results showed that women are healthier than men and in spite of all the considerations made, we concluded that there was a correlation between the two analyzed indices (BMI and BP).
Keywords: Obesity; blood pressure; body mass index